Methods for Improving Representativeness in a Web Survey on Sexual Assault Among College Students. Issue 23 (December 2019) - Berzofsky, Marcus E.; Langton, Lynn; Krebs, Christopher; Lindquist, Christine; Planty, Michael
Many colleges and universities conduct web-based campus climate surveys to understand the prevalence and nature of sexual assault among their students. When designing and fielding a web survey to measure a sensitive topic like sexual assault, methodological decisions, including the length of the field period and the use or amount of an incentive, can affect the representativeness of the respondent sample leading to biased or imprecise estimates. This study uses data from the Campus Climate Survey Validation Study (CCSVS) to assess how the interaction between field period length and survey incentive amount affects nonresponse, sample representativeness, and the precision of survey estimates. Research suggests that using robust incentives gives potential survey respondents a reason to complete the survey beyond their intrinsic motivation to do so. Likewise, extending the field period gives more time to people who may be less intrinsically motivated to complete the survey. Both serve to increase sample size and representativeness, minimize bias, and improve estimate precision. Schools, however, sometimes lack the time and/or resources for both a robust incentive and a lengthy field period, and this study examines the extent to which the potential negative impacts of not using one can be mitigated by the presence of the other. Findings indicate that target response rates can be achieved using a smaller incentive if the field period is lengthy but, even with a lengthy field period, the use of a smaller incentive can result in biased estimates due to a lack of representativeness. Conversely, when a robust incentive is used and weights are developed to adjust for nonresponse, a shorter field period will not have a significant impact on point estimates, but the estimates will be less precise due to fewer respondents participating in the survey.